When is Deceptive Message Production More Effortful than Truth-Telling? A Baker’s Dozen of Moderators - Burgoon, Judee K. (Frontiers in Psychology, 2015)
Deception is thought to be more effortful than telling the truth. Empirical evidence from many quarters supports this general proposition. However, there are many factors that qualify and even reverse this pattern. Guided by a communication perspective, I present a baker’s dozen of moderators that may alter the degree of cognitive difficulty associated with producing deceptive messages. Among sender-related factors are memory processes, motivation, incentives, and consequences. Lying increases activation of a network of brain regions related to executive memory, suppression of unwanted behaviors, and task switching that is not observed with truth-telling. High motivation coupled with strong incentives or the risk of adverse consequences also prompts more cognitive exertion–for truth-tellers and deceivers alike–to appear credible, with associated effects on performance and message production effort, depending on the magnitude of effort, communicator skill, and experience. Factors related to message and communication context include discourse genre, type of prevarication, expected response length, communication medium, preparation, and recency of target event/issue. These factors can attenuate the degree of cognitive taxation on senders so that truth-telling and deceiving are similarly effortful. Factors related to the interpersonal relationship among interlocutors include whether sender and receiver are cooperative or adversarial and how well-acquainted they are with one another. A final consideration is whether the unit of analysis is the utterance, turn at talk, episode, entire interaction, or series of interactions. Taking these factors into account should produce a more nuanced answer to the question of when deception is more difficult than truth-telling.